Experimental and numerical studies of a novel asymmetric nonlinear mass damper for seismic response mitigation. Issue 4 (10th January 2020) - Wang, Jingjing; Wang, Bin; Liu, Zhibin; Zhang, Chao; Li, Haobo
Summary: This paper proposes a novel passive mass damper, namely, asymmetric nonlinear energy sink (Asym NES), which is characterized by integrating linear and nonlinear restoring forces to mitigate the unwanted responses of building structures. The Asym NES, configured based on a cubic NES, consists of an auxiliary mass connected to the primary structure through a linear and nonlinear springs. These two springs are statically balanced at a deformed position, producing an asymmetric restoring force in the Asym NES. The study commences with a detailed working principle of the Asym NES, and the equations of motion of an Asym NES‐attached system are derived. Subsequently, experimental studies on the Asym NES designed for a small‐scale three‐story steel frame are conducted; the natural frequencies of which can be altered by changing the number of columns per story. Moreover, the performance of the Asym NES is compared with a tuned mass damper (TMD) and a cubic NES under impulsive excitations. Test results demonstrate the effectiveness of the Asym NES as well as its robustness against changes in the structural frequency. Following the experimental studies, the validated Asym NES model is further applied in the numerical investigation on a six‐story benchmark building to highlight its effectiveness and robustness in potential practical applications. Besides the impulsive excitations, an ensemble of 106 seismic ground motions with wide‐ranged energies is applied to the structures with original and decreased frequencies. Numerical results show that the proposed Asym NES is as effective as the in‐tune TMD in response mitigation under seismic excitations and exhibits strong robustness against changes in both the energy level and the structural frequency. The ingenious design and excellent efficiency of the Asym NES can offer a promising type of high‐performance device for structural control under extreme events.